1 - Black Hawk Down and the Framing of Somalia: Pop Culture as News and News as Pop Fiction - Peter Kareithi; Nixon Kariithi (Africa Media Review, 2008)
Barely one month before leaving office, President George H. W. Bush ordered 28,000 American troops into Somalia. It was the largest American humanitarian operation in many years. The operation was intended to halt the starvation of thousands of Somali civilians caught in the crossfire of warring factions jockeying for power following the collapse of the country’s central government. In the end, the operation failed. This paper seeks first, to examine the basis and nature of the framing of this event by American news and entertainment media during the American adventure in Somalia and in the aftermath of the events of September 11, 2001, and second, to explore the image of the Somali created in the American public mind by this framing.